Hypsodonty and tooth facet development in relation to diet and habitat in herbivorous ungulates: implications for understanding tooth wear. (15th November 2011) - Kaiser, Thomas M.; Müller, Dennis W. H.; Fortelius, Mikael; Schulz, Ellen; Codron, Daryl; Clauss, Marcus
Abstract The evolution of high‐crowned teeth or hypsodonty in herbivorous mammals is widely interpreted as a species‐specific adaptation to increasingly wear‐inducing diets and environments at evolutionary time scales, with internal abrasives (such as phytoliths in grasses) and/or external abrasives (such as dust or grit) as putative causative factors. The mesowear score (MS) instead describes tooth wear experienced by individual animals during their lifetime. Under the assumption that the abrasiveness that causes the MS in individuals is the same abrasiveness to which species adapted by evolving hypsodonty, one would expect a close correlation between the MS and the hypsodonty index (HI). Alternatively, if these two measures reflect different aspects of wear, one would expect differences in the way that proxies of diet or environment/climate correlate with each parameter. In order to test these hypotheses, we collated a dataset on the HI, MS, percentage of grass in the natural diet (%grass), habitat (open, intermediate, closed) and annual precipitation (PREC) in extant mammalian herbivores. The availability of a quantitative MS constrained the dataset to 75 species. Data were analysed with and without phylogenetic generalized least squares. Correlations with PREC were stronger for HI than for MS, whereas correlations with %grass were similar for HI and MS. Habitat had a significant influence on the relationship with %grass for HI but not for MS. Habitat also had a significant influence on the relationship between HI and MS. MS improved the predictive power of HI for %grass, but not for PREC. These results suggest that while the MS indicates predominantly the wear effect of the diet (internal abrasives), HI represents an adaptation to a wear effect that comprises both diet and environment (external abrasives). The additional environmental wear effect must reduce tooth height without causing macroscopic changes in tooth facet development as described by the MS. The most parsimonious explanation for the apparent discrepancy between HI and MS is that external abrasives of very fine particle size play a major role in naturally occurring tooth wear. The experimental testing of this hypothesis will enhance our understanding of the processes involved in tooth wear.